Evaluation of Immunomodulatory Effects of Mesenchymal Stem Cells Soluble Factors on miR-155 and miR-23b Expression in Mice Dendritic Cells. (July 2015) - Karachi, Aida; Fazeli, Mehdi; Karimi, Mohammad Hossein; Geramizadeh, Bita; Moravej, Ali; Ebrahimnezhad, Salimeh; Afshari, Afsoon
<x xml:space="preserve">Abstract</x> Mesenchymal stem cells (MSCs) can modulate dendritic cells (DCs) activation and induce tolerogenic characteristics in DCs. All mechanisms involved in MSCs-induced tolerogenic DCs are not fully understood. MicroRNAs (miRs) play important role in maturation and function of DCs. In this study, we investigated the effects of MSCs culture supernatant (C.S.) on expression of miR-155 and miR-23b in mice DCs. BALB/c mice spleens were used for DCs isolation. MSCs were isolated from the mice bone marrow and cultured in DMEM media. When MSCs expanded to sixth passage, C.S. was collected after 12, 24 and 48 h. Quantitative polymerase chain reaction (QPCR) was used to determine the expression of miR-155 and miR-23b in DCs treated with C.S. after 6 and 12 h. Secretion of IL-23 and TGF- β were detected in DCs treated with C.S. by ELISA after 24 h. miR-23b expression was significantly increased in DCs treated with 12 h C.S. for 12 h compared to negative controls. miR-155 expression did not change in DCs treated with C.S. after 6 and 12 h. miR-23b expression was significantly increased in DCs treated with 12 h C.S. for 12 h, compared to those treated with C.S. for 6 h. Similarly, miR-23b expression was increased in DCs treated with 24 h C.S. for 12 h when compared to those treated for 6 h. Production of TGF-β and IL-23 were not influenced by C.S. In conclusion, miR-23b is considered to be one of the mechanisms involved in tolerogenic DCs induction by C.S. in a time-dependent manner.